Sound and spirit - Tabanli, Mustafa (New Jersey : Everest Production, 2008)
Sound and music are powerful influences that can bring us to heightened states of awareness and bliss or slowly and steadily wear down our emotional and physical health. Today, in many areas of the world, we're exposed to constant sound or noise and therefore in a constant state of stress - what price are we paying? And, what can we do about it? This program features a number of experts who will share their perspectives about how we can harness the power of sound and music to soothe our spirits, and heal our bodies and our minds.
Executive producer, Nasuhi yurt.
Host : MaryLynn Schiavi.
DVD format.
Keywords: Music therapy; Music -- Psychological aspects; Sound